2016
DOI: 10.1016/j.brat.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental psychopathology paradigms for alcohol use disorders: Applications for translational research

Abstract: In spite of high prevalence and disease burden, scientific consensus on the etiology and treatment of Alcohol Use Disorder (AUD) has yet to be reached. The development and utilization of experimental psychopathology paradigms in the human laboratory represents a cornerstone of AUD research. In this review, we describe and critically evaluate the major experimental psychopathology paradigms developed for AUD, with an emphasis on their implications, strengths, weaknesses, and methodological considerations. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 205 publications
(241 reference statements)
0
28
0
Order By: Relevance
“…Future studies could investigate the role of other hypothesized moderators and mediating mechanisms within this comprehensive model (Craske, 2016), or just focus on one of the manipulations in greater detail. Future translational research could employ EPIIC to evaluate the specific effects of intervention techniques within a controlled context (Bujarski & Ray, 2016). It is hoped such efforts will eventually inform new approaches to early intervention with impulsive youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies could investigate the role of other hypothesized moderators and mediating mechanisms within this comprehensive model (Craske, 2016), or just focus on one of the manipulations in greater detail. Future translational research could employ EPIIC to evaluate the specific effects of intervention techniques within a controlled context (Bujarski & Ray, 2016). It is hoped such efforts will eventually inform new approaches to early intervention with impulsive youth.…”
Section: Discussionmentioning
confidence: 99%
“…Primary outcomes of interest were administered as repeated measures in order to reduce the potential impact of individual differences on induction effects. Laboratory alcohol consumption is influenced by body weight, sex, alcohol metabolism, drinking history, and many other factors that can be controlled for in a within-subjects design (Bujarski & Ray, 2016). The moderating effect of a heavy-drinking peer on alcohol consumption was also incorporated, such that half of all participants will engage in laboratory consumption with a confederate across both sessions (or not; between-subjects).…”
Section: Introductionmentioning
confidence: 99%
“…The following well-validated (Bujarski and Ray, 2016;Mason and Higley, 2013) experimental paradigms were implemented to examine medication effects on subjective response to alcohol, cue reactivity, and stress reactivity:…”
Section: Experimental Procedures and Measuresmentioning
confidence: 99%
“…The third category consists of alcohol self-administration paradigms in which individuals are given the opportunity to consume alcohol in the laboratory. As discussed in detail elsewhere, each paradigm has its own strengths and weaknesses (Bujarski and Ray, 2016), and can be leveraged to address a multitude of research questions (Ray et al, 2016). While the aforementioned experimental methods are widely used in the field of alcohol research, surprisingly few studies have examined the associations between subjective response to alcohol, craving for alcohol, and alcohol self-administration within individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective response to alcohol represents a multifaceted (Ray et al, 2009, Bujarski et al, 2015b and replicable construct (Roche et al, 2014, King et al, 2015. Moreover, alcohol administration methods include both intravenous and oral alcohol administration, with the first benefiting from tight controls over breath alcohol concentration (BrAC) and the later benefiting from greater ecological validity (Bujarski and Ray, 2016). While there are few direct comparisons of the two methods, an early study found them comparable in eliciting subjective response with the exception of craving which was significantly higher in the oral alcohol administration model (Ray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%